POST-COVID SEQUELAE: THE BUMMOCK OF COVID ICEBERG - KP, MOHANRAJ; KM, ASNEEM; CHERIAN, MERIN; NAHID; ARAFATH S, YASAR (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Coronavirus disease of 2019 (COVID-19) is a highly transmissible and pathogenic infection caused by severe acute respiratory syndrome, which resulted in a global pandemic and a significant loss of human life. The newer variants of concern are evolving even with the broadening vaccine immunity. Much of the clinical course remains uncertain especially the possible long-term health consequences. It is observed that there is an inter-individual variability in the occurrence of these post-COVID symptoms. Methods: A prospective observational survey was conducted to demonstrate the post-COVID-19 manifestations and to identify if there is any association of these manifestations with the disease severity and presence of comorbidities. Results: About 85% of our study subjects reported post-COVID manifestations of varying degrees. Fatigue was the most common post-COVID manifestation reporting to 56.36%. This was followed by body ache (43.3%) and myalgia (36.81%). The least observed manifestations were myocarditis (1.81%), heart attack (1.36%), and vomiting (1.36%). Conclusion: An association between the severity of COVID disease and comorbidities was identified. The surface plot graph signified the existence of a positive association between the post-COVID manifestations with the severity of disease and the presence of comorbidities. The functional outcomes of the subjects after recovery were assessed using a post-COVID functional status scale.